Medical imaging using ionizing radiation: Optimization of dose and image quality in fluoroscopy - Jones, A. Kyle; Balter, Stephen; Rauch, Phillip; Wagner, Louis K. (Medical physics (Lancaster), 2014)
The 2012 Summer School of the American Association of Physicists in Medicine (AAPM) focused on optimization of the use of ionizing radiation in medical imaging. Day 2 of the Summer School was devoted to fluoroscopy and interventional radiology and featured seven lectures. These lectures have been distilled into a single review paper covering equipment specification and siting, equipment acceptance testing and quality control, fluoroscope configuration, radiation effects, dose estimation and measurement, and principles of flat panel computed tomography. This review focuses on modern fluoroscopic equipment and is comprised in large part of information not found in textbooks on the subject. While this review does discuss technical aspects of modern fluoroscopic equipment, it focuses mainly on the clinical use and support of such equipment, from initial installation through estimation of patient dose and management of radiation effects. This review will be of interest to those learning about fluoroscopy, to those wishing to update their knowledge of modern fluoroscopic equipment, to those wishing to deepen their knowledge of particular topics, such as flat panel computed tomography, and to those who support fluoroscopic equipment in the clinic.